2008
DOI: 10.1021/ja710132c
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Control for the Modular Synthesis of Pseudopeptidic Macrocycles through an Anion-Templated Reaction

Abstract: Registro de acceso restringido Este recurso no está disponible en acceso abierto por política de la editorial. No obstante, se puede acceder al texto completo desde la Universitat Jaume I o si el usuario cuenta con suscripción. Registre d'accés restringit Aquest recurs no està disponible en accés obert per política de l'editorial. No obstant això, es pot accedir al text complet des de la Universitat Jaume I o si l'usuari compta amb subscripció. Restricted access item This item isn't open access because of publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 93 publications
(52 citation statements)
references
References 135 publications
(46 reference statements)
0
51
0
Order By: Relevance
“…In this context, pseudopeptidic compounds are good receptors of anions due to the coordination properties of the amide groups [2,3]. For this purpose, the preorganization provided by macrocyclic structures is important, and the preparation of such structures from C 2 pseudopeptidic bis(amidoamines) has been investigated in detail in our research group [4][5][6][7]. Previous studies focused on compounds such as 1 (Scheme 1) [4].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, pseudopeptidic compounds are good receptors of anions due to the coordination properties of the amide groups [2,3]. For this purpose, the preorganization provided by macrocyclic structures is important, and the preparation of such structures from C 2 pseudopeptidic bis(amidoamines) has been investigated in detail in our research group [4][5][6][7]. Previous studies focused on compounds such as 1 (Scheme 1) [4].…”
Section: Introductionmentioning
confidence: 99%
“…During our research on the supramolecular chemistry of simple pseudopeptidic compounds [18][19][20][21][22][23], we screened the crystallization conditions of several different N-protected dipeptide sequences. Thus, we observed that when the Z-AF-OH dipeptide was placed in a MeOH solution containing an excess of 12 N HCl, large crystals appeared after very long time (several months).…”
Section: Resultsmentioning
confidence: 99%
“…During our ongoing research program in the field of pseudopeptidic compounds [18,19], we became interested in the self-aggregation process of the molecules through non-covalent interactions [20][21][22]. Within this field, the peptidic sequence Z-AF-OH appeared as an interesting target for molecular recognition by synthetic pseudopeptidic macrocycles [23].…”
Section: Open Accessmentioning
confidence: 99%
“…Anions are less often employed in template syntheses because of their undesirable features, which include a high solvation energy, a low charge to radius ratio and a high pH dependence. Several examples of anion-assisted formation of rotaxanes and similar macromolecules are found in the literature [12]. The only multi-component anionic template to our knowledge was reported by Rubio and coworkers [12] in the synthesis of macrocycles derived from amino acids.…”
Section: Introductionmentioning
confidence: 99%